Synthesis of Magnesium Carbonate with Bittern Raw Material with Carbon Dioxide Gas Injection in Packing Column (Nusantara Science and Technology Proceedings)
Magnesium carbonate is known as magnesite, which is naturally a carbonate of magnesium compounds, the main raw material for magnesium oxide (magnesia). Magnesium carbonate has many uses, one of which is an additive in the pharmaceutical field used as an additive for laxatives. In this research, magnesium carbonate is forming magnesium hydroxide by mixing bittern and sodium hydroxide 1,875 N then reacting magnesium hydroxide and carbon dioxide gas in a packed column reactor. This study aims to determine the best flow rate and contact time ratio, the factors that influence, and the amount of magnesium carbonate formed. The variables used are carbon dioxide gas flow rate and contact time. The best results from this study were obtained with a flow rate of 2 liters/minute with a contact time of 30 minutes obtained 72% magnesium carbonate levels.